2017
DOI: 10.1161/jaha.116.004346
|View full text |Cite
|
Sign up to set email alerts
|

Translocase of Inner Membrane 50 Functions as a Novel Protective Regulator of Pathological Cardiac Hypertrophy

Abstract: BackgroundTranslocase of inner membrane 50 (TIM50) is a member of the translocase of inner membrane (TIM) complex in the mitochondria. Previous research has demonstrated the role of TIM50 in the regulation of oxidative stress and cardiac morphology. However, the role of TIM50 in pathological cardiac hypertrophy remains unknown.Methods and ResultsIn the present study we found that the expression of TIM50 was downregulated in hypertrophic hearts. Using genetic loss‐of‐function animal models, we demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…It has been reported that interactions of peptides with TIM50 are weakened in the presence of Ca 2+ 40 . TIM50 is downregulated in both human dilated cardiomyopathy and murine hypertrophic hearts 41 . Consistent with this finding, we also found a downregulation of TIMM50 in cardiac rejection.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that interactions of peptides with TIM50 are weakened in the presence of Ca 2+ 40 . TIM50 is downregulated in both human dilated cardiomyopathy and murine hypertrophic hearts 41 . Consistent with this finding, we also found a downregulation of TIMM50 in cardiac rejection.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, Tim50 in other eukaryotes, like mammals, insects, plants, and fish, possesses this motif, and human Tim50 showed phosphatase activity (1517). It has been reported that besides mitochondrial protein import, Tim50 is involved in various cellular functions in these organisms, such as steroidogenesis in gonadal tissues (18), protection of cardiac cells from cardiac hypertrophy (19), apoptosis and developmental regulation in Drosophila and zebrafish (15, 16), growth and proliferation in plants (17), and chemoresistance in cancer cells (20). It is known that Tim50 maintains the permeability barrier of the MIM; therefore, over- or underexpression of Tim50 hampers mitochondrial function by hyperpolarization or depolarization of the mitochondrial membrane, respectively (12).…”
Section: Introductionmentioning
confidence: 99%
“…However, cardiac involvement is a characteristic finding of BS (Barth et al, 1983;Bione et al, 1996) and of patients with mutations in DNAJC19 (Davey et al, 2006). Several studies in animal models have proposed a role for TIMM50 in the pathogenesis of heart dysfunction and have shown that TIMM50-deficient mice have cardiac hypertrophy (Tang et al, 2017). On the other hand, inactivation of the TIMM50 protein ortholog in zebrafish results in brain malformations and heart abnormalities (Guo et al, 2004).…”
Section: Discussionmentioning
confidence: 99%